2018
DOI: 10.1016/j.neuron.2018.06.022
|View full text |Cite
|
Sign up to set email alerts
|

OLMα2 Cells Bidirectionally Modulate Learning

Abstract: Inhibitory interneurons participate in mnemonic processes. However, defined roles for identified interneuron populations are scarce. A subpopulation of oriens lacunosum-moleculare (OLM) interneurons genetically defined by the expression of the nicotinic receptor α2 subunit has been shown to gate information carried by either the temporoammonic pathway or Schaffer collaterals in vitro. Here we set out to determine whether selective modulation of OLMα2 cells in the intermediate CA1 affects learning and memory in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 48 publications
2
39
0
Order By: Relevance
“…The OLM cells are known to fire at the trough of theta oscillation, but can be silent during the sharp wave-associated ripples (SWRs) via yet unknown mechanisms [4][5][6][7]19]. By inhibiting distal and disinhibiting proximal dendrites of CA1 PCs, OLM cells have been considered essential for modulating the integration of the temporoammonic (TA) vs Schaffer collaterals (SC) inputs [20][21][22][23], burst firing of PCs [24,25] and generation of theta oscillations in vitro [26][27][28] and in vivo in the ventral hippocampus [29]. Thus, given that synchronous activation of IS3 cells is capable of pacing the OLM interneuron activity at theta frequency [18], the IS3 input to OLM cells may act as a gear mechanism providing for rhythmic gating of the SC vs TA inputs in the CA1 area.…”
Section: Introductionmentioning
confidence: 99%
“…The OLM cells are known to fire at the trough of theta oscillation, but can be silent during the sharp wave-associated ripples (SWRs) via yet unknown mechanisms [4][5][6][7]19]. By inhibiting distal and disinhibiting proximal dendrites of CA1 PCs, OLM cells have been considered essential for modulating the integration of the temporoammonic (TA) vs Schaffer collaterals (SC) inputs [20][21][22][23], burst firing of PCs [24,25] and generation of theta oscillations in vitro [26][27][28] and in vivo in the ventral hippocampus [29]. Thus, given that synchronous activation of IS3 cells is capable of pacing the OLM interneuron activity at theta frequency [18], the IS3 input to OLM cells may act as a gear mechanism providing for rhythmic gating of the SC vs TA inputs in the CA1 area.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that OLM cells play a gating role ( Leão et al, 2012 ), akin to earlier work by Blasco-Ibáñez and Freund (1995) who showed that “horizontal SOM+ interneurons” (i.e., putative OLM cells) could act as a switch controlling activation of local pyramidal cells via Schaeffer collaterals or perforant path input from entorhinal cortex. Further work has shown that OLM cells in intermediate regions of CA1 exert a bidirectional control on learning and memory ( Siwani et al, 2018 ), and ventral OLM cells control Type 2 theta rhythms and are associated with increased risk-taking ( Mikulovic et al, 2018 ). In a recent modeling study, OLM cells were shown to be critical in producing a robust intrinsic theta output ( Chatzikalymniou and Skinner, 2018 ), which suggests that their neuromodulation may be key to the maintenance of theta rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent study found CA1 OLM cells to follow theta‐frequency inputs independently of I h (Kispersky, Fernandez, Economo, & White, ). However, the aforementioned studies do not report the specific location of investigated OLM cells along the dorsoventral hippocampal axis, while a recent study (Siwani et al, ) demonstrated that OLM α2 cells from the intermediate hippocampus show larger depolarization in response to nicotine than DH OLM α2 interneurons. These results indicate differential biophysical properties of OLM interneurons along the septotemporal hippocampal axis.…”
Section: Introductionmentioning
confidence: 95%
“…Modeling studies have suggested that oriens lacunosum moleculare (OLM) interneurons are essential to hippocampal theta rhythmogenesis through feedback inhibition (Hummos, Franklin, & Nair, ; Neymotin et al, ; Tort, Rotstein, Dugladze, Gloveli, & Kopell, ). OLM cells, together with bistratified cells that target different dendritic compartments of PCs than OLM cells (Müller & Remy, ), contribute to behaviors where gating of information is important for the functional output of the hippocampus (Katona et al, ; Leão et al, ; Lovett‐Barron et al, ; Mikulovic et al, ; Siwani et al, ). The OLM neuron is characterized based on its morphological features and slow accommodating firing (Leão et al, ), and recently several genetic markers have been evaluated for targeting OLM cells (Chittajallu et al, ; Leão et al, ; Mikulovic, Restrepo, Hilscher, Kullander, & Leão, ; Taniguchi et al, ).…”
Section: Introductionmentioning
confidence: 99%